KRITERIA PEMILIHAN JENIS KAYU SEBAGAI BAHAN BAKU ALAT MUSIK GITAR AKUSTIK BERDASARKAN PERSEPSI MASYARAKAT DI KECAMATAN SIPOHOLON KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA - Dame R Pakpahan; Rudianda Sulaeman; M. Mardhiansyah M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Acoustic guitar as musical instrument is a precious asset for people in Sipoholon Subdistrict that its existence must be preserved and becomes a characteristic in manufacturing by using selected woods. This research aims to determine what kind of woods and criteria of woods that community use as raw materials of acoustic in Sipoholon Subdistrict. The used data analysis was used descriptive with quantitative data through guestionnaires and interviews to the community of Sipoholon Subdistrict and determined by snowball sampling. The results of this research indicate that there are 5 woods plant that used as acoustic guitar material, such as Dyera costulata, Toona sureni, Artocarpus heterophylus Lamk, Pinus merkusii, swietenia macrophylla. The wood priority that community use in Sipoholon Subdistrict is Dyera costulata. The woods criteria that used to acoustic guitar production is the plants that have diameter up to 30 cm and straightness level 80%.Keywords: types woods, criteria of woods, acoustic guitar, public perception